Importância do núcleo parabraquial lateral no controle do equilíbrio hidromineral em modelo animal de hipertensão essencial - Guillen, Camilla Dias (2018)
Excessive salt intake has been associated with the development or worsening of chronic diseases such as hypertension. Spontaneously hypertensive rats (SHR) have a typical increased sodium preference. The lateral parabrachial nucleus (LPBN) acts as an important inhibitory mechanism for sodium intake control, besides its involvement in cardiovascular control in normotensive rats. However, the involvement of LPBN in cardiovascular control and sodium appetite is still unknown in SHR. The aim for the present study was to evaluate cardiovascular responses and 0.3 M NaCl intake after α2-adrenergic receptors activation in LPBN in this model of essential hypertension. In SHR, bilateral injections of moxonidine (α2-adrenergic/imidazolinereceptors agonist) in LPBN increased 0.3 M NaCl intake induced by water deprivation – partial rehydration protocol (WD-PR), without changes in water intake. However, LPBN moxonidine injections did not significantly change 0.3 M NaCl or water intake induced by WD-RP in normotensive Holtzman rats. In normohydrated SHR moxonidine injections into the LPBN did not change 0.3 M NaCl and water intake, mean arterial pressure (MAP), heart rate (HR) and baroreflex responses. The WD-PR protocol did not change baseline values of MAP and HR in SHR, neither after LPBN moxonidine injections. It was also observed that LPBN moxonidine injections in SHR resulted in a positive sodium balance, characterized by increased 0.3 M NaCl intake during the sodium appetite test followed by increased renal sodium excretion and urinary volume at the end of the experiment. Therefore, present results show thatα2-adrenergic/imidazolinereceptors activation in the LPBN increases WD-PR-induced sodium appetite in SHR. This effectis not related to changes in arterial pressure. Therefore, we can conclude that LPBN inhibitory mechanisms contribute to limit sodium intake also in Spontaneously Hypertensive Rats.